4(5x-1)-5(5x-3)=

Simple and best practice solution for 4(5x-1)-5(5x-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5x-1)-5(5x-3)= equation:


Simplifying
4(5x + -1) + -5(5x + -3) = 0

Reorder the terms:
4(-1 + 5x) + -5(5x + -3) = 0
(-1 * 4 + 5x * 4) + -5(5x + -3) = 0
(-4 + 20x) + -5(5x + -3) = 0

Reorder the terms:
-4 + 20x + -5(-3 + 5x) = 0
-4 + 20x + (-3 * -5 + 5x * -5) = 0
-4 + 20x + (15 + -25x) = 0

Reorder the terms:
-4 + 15 + 20x + -25x = 0

Combine like terms: -4 + 15 = 11
11 + 20x + -25x = 0

Combine like terms: 20x + -25x = -5x
11 + -5x = 0

Solving
11 + -5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + -5x = 0 + -11

Combine like terms: 11 + -11 = 0
0 + -5x = 0 + -11
-5x = 0 + -11

Combine like terms: 0 + -11 = -11
-5x = -11

Divide each side by '-5'.
x = 2.2

Simplifying
x = 2.2

See similar equations:

| 3x-6+6x+12=12x-24 | | 16/72=x/1416 | | -3+6=39 | | 4.9t^2-26t-10=0 | | 6f+2=20 | | -6(3x-5)=19(7-x) | | -6m+3=10-5m | | -2(3x+5)+4(2x+2)= | | 2x^3-10x^2-100x=72 | | 4y-4+y+24=6y-20-4y | | -17=-31-7f | | (268*366)/(4400*156) | | 3-(2x+5)=5+x+2(4-6) | | -104/-8x | | x-9=5x+15 | | (8+4q)(-9)= | | (4x-6)=90and(2x) | | 30-2x+6x+22=90 | | 5-3x=-11+x | | -x+38=2x+17 | | 8(x+4)+10=10x-2(x-5) | | 7.84cm= | | 7.84= | | -2x+14=x+2 | | x^2+7x+36.75=0 | | 3x-2=20-x | | 4-2c=8 | | -5x-29=145 | | (4x+3)*(3x+2)=0 | | x+6x-1=90 | | (4x-3)*(3x-2)=0 | | 3(2q+3)=5(2q+1) |

Equations solver categories